Sigatoka leaf spot diseases: Black leaf streak disease (black Sigatoka); Sigatoka disease (yellow Sigatoka) - Mourichon, X.; Carlier, J.; Fouré, E.; International Network for the Improvement of Banana and Plantain (1997)
Musa disease fact sheet on Sigatoka leaf spot diseases (black and yellow). The black leaf streak disease caused by Mycosphaerella fijiensis and the Sigatoka disease caused by Mycosphaerella musicola. This double sheet provides updated information on the distribution of the two diseases and reviews the most recent research information and requirements: symptoms, control measures and breeding for resistance.